A legal perspective on development on strata management in peninsular Malaysia: a review of the Strata Titles Act 1985 (UP 054) - Mohamad, Mazliza; Sufian, Azlinor; Mohamad, Nor Asiah (2011)
The strong growth of Malaysia's economy in over the last 20 years has led to the increase in urbanization which resulted in changes in the property development. Due to scarcity of land, the housing development tremendously changed from horizontal to vertical approach. In order to facilitate this development, the Strata Titles Act 1985 (Act 318) ("STA") was introduced to regulate matters related to strata buildings inter alia on the management and maintenance of common properties. The STA has been in existence nearly 26 years and has been amended several times. Nevertheless the problem of maintenance and management of strata building continues to be on of the biggest problems in the building industry in Peninsular Malaysia. For instance, there have been numerous complaints on maintenance and management issues involving the developer and parcel owners. The objective of this paper is to review the legal aspects of the strata management as stipulated in the STA. It is to be noted that this paper is mainly focused on the evaluation of legal provisions of statutes. The research method used in writing this paper is the qualitative research in which it will rely on the analysis of the relevant statutes, rules, regulations, books, journals, articles, thesis, monograph, research grants reports, seminar papers, electronic materials and various newspaper reports.